2007
DOI: 10.1152/physiolgenomics.00190.2006
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression response of the rat small intestine following oral Salmonella infection

Abstract: Data on the molecular response of the intestine to the food-borne pathogen Salmonella are derived from in vitro studies, whereas in vivo data are lacking. We performed an oral S. enteritidis infection study in Wistar rats to obtain insight in the in vivo response in time. Expression profiles of ileal mucosa (IM) and Peyer's patches (PP) were generated using DNA microarrays at days 1, 3, and 6 postinfection. An overview of Salmonella-regulated processes was obtained and confirmed by quantitative real-time PCR o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
4
29
1
Order By: Relevance
“…Profiling of host gene expression has also been used to examine the host immune response to Salmonella infection, in particular, in cultured host cells such as murine macrophages (59) and human intestinal epithelial cells (15), in both of which Salmonella was shown to induce numerous proinflammatory genes. It was recently shown that, in contrast to the large extent of differentially modulated genes observed in these in vitro studies, oral infection with Salmonella induces few proinflammatory gene expression changes in the rat small intestine (58). Nevertheless, the disparities between the Salmonella strains, cell lines, organs, or animals used, together with the types of genes analyzed in these studies, make direct comparison to our results difficult.…”
Section: Discussioncontrasting
confidence: 70%
“…Profiling of host gene expression has also been used to examine the host immune response to Salmonella infection, in particular, in cultured host cells such as murine macrophages (59) and human intestinal epithelial cells (15), in both of which Salmonella was shown to induce numerous proinflammatory genes. It was recently shown that, in contrast to the large extent of differentially modulated genes observed in these in vitro studies, oral infection with Salmonella induces few proinflammatory gene expression changes in the rat small intestine (58). Nevertheless, the disparities between the Salmonella strains, cell lines, organs, or animals used, together with the types of genes analyzed in these studies, make direct comparison to our results difficult.…”
Section: Discussioncontrasting
confidence: 70%
“…Both microbial infections of conventional mice and intestinal colonization of germ-free mice by commensals increase ileal expression of the secreted C-type lectins Reg3g and Reg3b (3,12,22,25). While Reg3g has been shown to have a bactericidal activity against Gram-positive bacteria (3), the physiological function of Reg3b remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Reg3g and Reg3b expression was determined in the ileum because this is the area where expression is upregulated during infection of rats (22,25) and upon microbial colonization of germ-free mice (3). Frozen mucosal scrapings of the ileum were pulverized under liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes upregulated in the human intestinal epithelial cell line HT-29 infected with S. enterica serovar Dublin for 3, 8, or 20 h, included several cytokines (G-CSF, Inhibin βA, EBI3, MIP-2α, IL-8), kinases (TKT, Eck, HEK), transcription factors (IRF-1), and HLA class I [119]. Other interesting examples of global in vitro and in vivo studies are the gene expression profiling in chicken heterophils infected with S. enterica serovar Enteritidis [120], the analysis of transcriptional responses to S. enterica serovar Choleraesuis infections in pig mesenteric lymph nodes [121], the analysis of the gene expression response of the rat small intestine following oral infection with S. enterica serovar Enteritidis [122], and the transcriptional profiles from S. enterica serovar Typhi-infected children [123]. However, the role of the T3SSs on host transcriptional responses was not investigated in these studies.…”
Section: Nuclearmentioning
confidence: 99%